Experimental and density functional theory studies on some metal oxides and the derived nanoclusters: a comparative effects on human ferritin - Zahraa S. Al-Garawi; Ahmad H. Ismail; Duaa H. Hillo; Füreya Elif Öztürkkan; Hacali Necefoğlu; Gehad G. Mohamed; Abanoub Mosaad Abdallah (Discover Nano, 2024)
Abstract A comprehensive investigation into the green synthesis of metal oxide nanoparticles (NPs) has garnered significant attention due to its commendable reliability, sustainability, and environmentally friendly attributes. Green synthesis methods play a crucial role in mitigating the adverse effects associated with conventional approaches employed for nanostructure preparation. This research endeavors to examine the impact of ginger plant extract-assisted green synthesis of metal oxides NPs on the serum ferritin levels of anemic diabetic patients in vitro, focusing specifically on α-Fe2O3 and ZnO NPs. Sixty diabetic volunteers with anemia (35–50 years) and thirty healthy volunteers were enrolled as controls. The assessment was conducted using the VIDAS Ferritin (FER) assay. Photoluminescence (PL) spectroscopy measurements were performed to elucidate the intrinsic and extrinsic transitions of these NPs, affirming the successful formation of α-structured iron oxide. Density functional theory (DFT) calculations were carried out at the B3LYP/6-311++G(d,2p) level of theory to investigate the geometry optimization and molecular electrostatic potential maps of the NPs. Furthermore, TD-DFT calculations were employed to explore their frontier molecular orbitals and various quantum chemical parameters. The binding affinity and interaction types of ZnO and α-Fe2O3 NPs to the active site of the human H-Chain Ferritin (PDB ID: 2FHA) target were determined with the help of molecular docking. Results unveiled the crystalline structure of ZnO and the α-structure of α-Fe2O3. Analysis of the frontier molecular orbitals and dipole moment values demonstrated that ZnO (total dipole moment (D) = 5.80 µ) exhibited superior chemical reactivity, biological activity, and stronger molecular interactions with diverse force fields compared to α-Fe2O3 (D = 2.65 µ). Molecular docking of the metal oxides NPs with human H-chain ferritin provided evidence of robust hydrogen bond interactions and metal-acceptor bonds between the metal oxides and the target protein. This finding could have a great impact on using metal oxides NPs-ferritin as a therapeutic protein, however, further studies on their toxicity are required. Graphical abstract